Metal-Free Nitrogen-Doped Carbon Foam Electrocatalysts for the Oxygen Reduction Reaction in Acid Solution. Issue 9 (12th July 2016) - Liu, J.; Yu, S.; Daio, T.; Ismail, M. S.; Sasaki, K.; Lyth, S. M.
Abstract : Metal-free, nitrogen-doped carbon foam is utilized as a model non-precious electrocatalyst system to investigate the role of nitrogen in the oxygen reduction reaction (ORR) in the absence of iron contamination. This graphene-like foam displays relatively high activity for the ORR in acid, despite being proven free from transition-metal impurities. The onset potential is 0.85 VRHE, the mass activity is 2.8 A/g at 0.6 VRHE, and the current density is −4.0 mA/cm 2 . The maximum electron transfer number is calculated to be 3.6, revealing that a 4-electron pathway is possible in nitrogen-doped carbon, even in the absence of transition-metal coordination sites. The excellent electrochemical activity is attributed to the large surface area (700 m 2 /g), improved conductivity after graphitization, and the relatively high proportion of tertiary (graphite-like) nitrogen.